EFEKTIFITAS PEMBERIAN EDUKASI NUTRISI PADA IBU HAMIL DALAM MENINGKATKAN PENGETAHUAN TENTANG STATUS GIZI DI POSKESDES PENAMPI KABUPATEN BENGKALIS - Tania, Nurul; Susanti, Komaria; Ekdeni Aifa, Wira; Tanberika, Fajar Sari (Ensiklopedia of Journal, 2025)
The low knowledge of pregnant women about pregnancy nutrition can have a negative impact on the health of the mother and fetus. Nutrition education is one of the potential promotive interventions to improve nutritional literacy of pregnant women, especially in rural areas such as Penampi Village Health Post, Bengkalis Regency. Objective: This study aims to determine the effectiveness of providing nutrition education on improving pregnant women's knowledge about nutritional status. Method: This study used a pre-experimental design with a one-group pretest-posttest approach. The sample consisted of 15 pregnant women selected using a purposive sampling technique. The instrument used was a nutrition knowledge questionnaire. Data were analyzed univariately and bivariately using the Paired Sample T-Test with a significance level of p < 0.05. Results: The results showed an increase in the average knowledge score from 59.93 (pre-test) to 82.60 (post-test). The statistical test showed a p value = 0.000, which means there was a significant difference between knowledge before and after education. The majority of pregnant women after education were categorized as having good knowledge (80%). Conclusion: Providing nutrition education has been proven effective in improving pregnant women's knowledge about nutritional status. This intervention is recommended as part of routine services at village health posts (Poskesdes) to increase nutritional awareness during pregnancy. Furthermore, it is recommended that Poskesdes develop interactive, culturally-based outreach methods, including the involvement of families and digital technology, to expand the reach and sustainability of nutrition education in the future.Keywords: Nutrition education, pregnant women, knowledge, nutritional status, Poskesdes